Assessing translational applicability of perineuronal net dysfunction in Alzheimer’s disease across species - Hendrickson, Aarun S.; Francis, Kendra L.; Kumar, Asmit; Le, Jaden P.; Scarlett, Jarrad M.; Keene, C. Dirk; Tovar, David A.; Alonge, Kimberly M. (Frontiers in Neuroscience, 2024)
In the context of aging and age-associated neurodegenerative disorders, the brain's extracellular matrix (ECM) serves as a critical regulator for neuronal health and cognitive function. Within the extracellular space, proteoglycans and their glycosaminoglycan attachments play essential roles in forming, stabilizing, and protecting neural circuits throughout neurodevelopment and adulthood. Recent studies in rodents reveal that chondroitin sulfate-glycosaminoglycan (CS-GAG) containing perineuronal nets (PNNs) exhibit both structural and compositional differences throughout the brain. While animal studies are illuminating, additional research is required to translate these interregional Deleted: PNN/CS-GAG variations to human brain tissue. In this perspective article, we first investigate the translational potential for interregional CS-GAG variances across species as novel targets for regionspecific therapeutic development. We specifically focus on the observation that alterations in brain PNN-associated CS-GAGs have been linked with the progression of Alzheimer's disease (AD) neuropathology in humans, but these changes have not been fully recapitulated in rodent models of this disease. A second highlight of this perspective article investigates whether AD-associated shifts in CS-GAGs in humans may be dependent on region-specific baseline differences in CS-GAG sulfation patterning. The current findings begin to disentangle the intricate relationships between the interregional differences in brain PNN/CS-GAG matrices across species, while emphasizing the need to better understand the close relationship between dementia and changes in brain CS-GAG sulfation patterns in patients with AD and related dementias.